PENGARUH INSENTIF DAN DISIPLIN KERJA TERHADAP SEMANGAT KERJA KARYAWAN (Studi Pada PT. Satria Primajaya Nusantara Handil Muara Jawa) - Dewi, Septira; Noorhaya. A.R.P, Eva (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Human resources (HR) is one of the main factors in global competition, namely how to create qualified and skilled human resources and have a culture of high competitiveness in global competition that we have ignored. Given the importance of the role of human resources in carrying out company activities, the company's management is required to always pay close attention to its workforce so that the morale achieved by employees increases and is in accordance with the company's targets in achieving its goals. The purpose of this study was to determine the effect of the incentive and work discipline variables simultaneously and partially on employee morale. The analytical tool used in this research is multiple regression, and the number of samples used is 70. The result of the research is that the incentive and discipline variables are simultaneously able to show a significant effect on employee morale. Partially, incentives have a significant effect on employee morale, and partially, discipline has a significant effect on employee morale.